An Examination of Radioactivity in the Crushed Rock from the PM-3A Nuclear Reactor Site, McMurdo, Antarctica. - Weiss,Herbert V (1976)
Radioactivity in McMurdo rock consists primarily of Cs137 and Sr90. The 6500 cu yds of affected material is estimated to contain 0.27 and 0.031 Ci of these two elements, respectively. Cs137, but not Sr90, is tenaciously bound to the rock in seawater. Both are held firmly by the rock in distilled water, thus, release to the environment would be significantly less in terrestrial rather than marine disposal.